Molecular Investigation of Quinolone Resistant Genes among Clinical Psedomonas aeruginosa Isolates - Zena T. wtwt; Eman M. Jarallah (Institute of Medico-legal Publications Pvt Ltd, 2021)
The current research was performed in Al-imam AL- Sadiq Hospital, Hilla Teaching Hospital, Babyloncity, Iraq to investigate the resistance gene of fluoroquinolones (FQs) in P. aeruginosa clinical isolatesof taken from different origins. Mutations arising at the bacterial gyrA, gyrB, parC, par E gene belong toDNA gyrase and topoisomerase IV are the fluoroquinolone tolerance essential mechanism in P. aeruginosa..and over expression of efflux pumps . (80) clinical isolates collected by Transport swabs from varioussource [(burn 45(56.25 %), wound 15 (18.75 %), ear 3 (3.75 %), blood 2 (2.5 %), urine 4(5 %),sputum11(13.75)] that initially identified by culturing on MacConkey agar, blood agar and cetrimide agar selectivemedia for Pseudomonas aeruginosa, P. aeruginosa chromogenic agar then diagnosed by performing somemorphological and biochemical tests. The second diagnosis to (10) isolates was done by VITEK 2 Compactsystem using VITEK 2GN,and by using PCR technique for genotyping detection by the 16s rRNA gene.A susceptibility test was applied to all (80) isolates using 9 antibiotics through resorting to Kirby-Pourmethod. The results of this test showed that isolates which represented the highest resistance to ciprofloxacin(71%),levofloxacin(75%) , aztreonam(87.5%), but isolates showed low resistance to impenem 18.75% and0%resistant to meropenem. (gyrA, gyrB) subunit of DNA gyrase is target of flouroquinolon antibiotic hasbeen screened by PCR reaction. The results showed that these genes present in P. aeruginosa at (100 percent,100 percent,), respectively..